MODEL OF SAMIZDAT AND THE CASE OF THE SPREAD OF SECRET PACTS OF RIBBENTROP–MOLOTOV - JASELIŪNAS, EGIDIJUS (Knygotyra, 2015)
The aim of the paper is to present the theoretical model of samizdat. With regard to this model, samizdat, which emerged in Lithuania in the 50’s of the 20th century and persisted nearly until the collapse of the soviet system, is construed as a new phenomenon of the underground press. Samizdat was one of the categories of the underground press, which was distinguished by a unique mechanism of spreading. With the reference to the insights of Aleksandr Daniel the first half of the paper discusses principal differences of samizdat from other categories of the underground press (“texts of personal usage”, “coterie”, partisan press and proclamations). Contrary to other underground press, the publishers of samizdat controlled only preparation and distribution of only the primary edition (generally small), and subsequent circulation of the publications took place in the circle of the readers. Therefore, the major role in samizdat was played by the readers, who multiplied and distributed the publications on their own initiative and without the awareness of the publishers.Pursuing to substantiate the presented theoretical model, the second half of paper scrutinizes Abstractthe history of the spread of one document – secret pacts of Ribbentrop–Molotov – in samizdat. The method of “one case analysis” revealed reasonability of the theoretical model and expedience of its use. The spread of the secret pacts of Ribbentrop–Molotov in the 70’s–80’s may be considered a typical model of samizdat. Moreover, the spread of the documents revealed a unique peculiarity of the renewal of samizdat: since samizdat was circulating in numerous directions and in a diversity of circles of readers, it was practically impossible for the soviet authorities to stop the spread of a text, which reached samizdat. Such elemental mistake predetermined vitality and efficiency of such underground press in the soviet society.Exchange of information through the principle of samizdat was determined by the heritage of the totalitarian political system – the society was so polarized that usual forms of the underground press become ineffective. In the meanwhile, samizdat opened new possibilities for the spread of the uncensored ideas in the post-totalitarian system, which could assist in overcoming mistrust prevailing in the society and its disunity.
Keywords: ...